Anti‐MRSA activity of oxysporone and xylitol from the endophytic fungus Pestalotia sp. growing on the Sundarbans mangrove plant Heritiera fomes. (29th November 2017) - Nurunnabi, Tauhidur Rahman; Nahar, Lutfun; Al‐Majmaie, Shaymaa; Rahman, S.M. Mahbubur; Sohrab, Md. Hossain; Billah, Md. Morsaline; Ismail, Fyaz M.D.; Rahman, M. Mukhlesur; Sharples, George P.; Sarker, Satyajit D.
Abstract : Heritiera fomes Buch.‐Ham., a mangrove plant from the Sundarbans, has adapted to a unique habitat, muddy saline water, anaerobic soil, brackish tidal activities, and high microbial competition. Endophytic fungal association protects this plant from adverse environmental conditions. This plant is used in Bangladeshi folk medicine, but it has not been extensively studied phytochemically, and there is hardly any report on investigation on endophytic fungi growing on this plant. In this study, endophytic fungi were isolated from the surface sterilized cladodes and leaves of H .  fomes . The antimicrobial activities were evaluated against two Gram‐positive and two Gram‐negative bacteria and the fungal strain, Candida albicans . Extracts of Pestalotia sp . showed activities against all test bacterial strains, except that the ethyl acetate extract was inactive against Escherichia coli . The structures of the purified compounds, oxysporone and xylitol, were elucidated by spectroscopic means. The anti‐MRSA potential of the isolated compounds were determined against various MRSA strains, that is, ATCC 25923, SA‐1199B, RN4220, XU212, EMRSA‐15, and EMRSA‐16, with minimum inhibitory concentration values ranging from 32 to 128 μg/ml. This paper, for the first time, reports on the anti‐MRSA property of oxysporone and xylitol, isolation of the endophyte Pestalotia sp. from H. fomes, and isolation of xylitol from a Pestalotia sp.